POSSIBLE PREDICTORS OF ATRIAL FIBRILLATION RECURRENCE IN LONG-TERM PROPHYLACTIC PROPAFENONE THERAPY - R. D. Kurbanov; N. U. Zakirov; Sh. K. Azizov; Kh. M. Raubzhanov (Столичная издательская компания, 2015)
Aim. To identify possible predictors of atrial fibrillation (AF) recurrence in 6-month prophylactic propafenone therapy. Material and methods. Patients (n=63; aged 52.2±12.6 years; 25.4% women) with frequent AF recurrences who restored sinus rhythm with propafenone, were included into the study. Paroxysmal AF was observed in 84.1% of patients, and persistent AF - in 15.9% of patients. ECG, transthoracic echocardiography , chest radiography with the calculation of cardio-thoracic index (CTI) was performed at baseline. All patients received rpropafenone therapy (450-600 mg/day) during 6 months after sinus rhythm conversion. ECG and 24-hours ECG monitoring were performed in 1, 3 and 6 months of the therapy. Patients with 70-100% reduction in AF recurrence rate were included into the 1-st group, and patients with <70% reduction - into the 2-nd group. Results. 92%, 88.5% and 78% of patients were included into the group 1 after 1, 3 and 6 months of follow up, respectively. AF recurrences were observed 4.5, 3.8, and 1.7 times more often in women than these in men after 1, 3 and 6 months, respectively , (p>0.05). Mean age of patients in the group 2 was significantly older than this in patients of the group 1 (p<0.05). CTI, left atrium size and volume, interventricular septum thickness (IVST) were significantly larger in group 2. Myocardium mass of the left ventricle (MMLV) after 6 months of therapy was larger by 13.9% in patients of the group 2 vs this in patients of the group 1 (p<0.05). Conclusion. Insufficient preventive effect of propafenone was observed in 8%, 11.5% and 22% of patients in 1, 3 and 6 months of the follow-up, respectively. Propafenone prophylactic efficacy was slightly higher in men and younger patients. Patients with poor preventive effect of propafenone had a significantly larger baseline CTI, size and volume of the left atrium, IVST, and MMLV.